IMPROVING THE ECONOMY OF THE COMMUNITY OF KADUMANGGU VILLAGE BY UTILIZING CASSAVA WASTE IN THE PROCESSING OF TAPIOCA FLOUR - Rosaliana, Dinda; Ayunniyah, Qurroh (LPPM Univ. Ibn Khaldun Bogor, 2022)
Research conducted in Kp. Lgk Nyenang Kadumanggu Village aims to find out how the general description of the processing of cassava into tapioca flour and the utilization of cassava waste into a use value. This study uses a qualitative method. The processing of cassava into tapioca flour consists of collecting raw materials, washing and peeling, grating, extraction, starch deposition, drying and milling. The rest of cassava waste, such as solid waste and liquid waste, can be used for something that has use value and can reduce pollution due to waste. The purpose of this research is to know the process of making tapioca flour from cassava and to analyze the utilization of residual waste to reduce environmental pollution. Solid waste from the process of making tapioca flour is cassava peel, and liquid waste is starch and elod water. Utilization of waste can be used as fertilizer, Asian flour, chips, crackers, and animal feed.